Uncrewed Vessels and International Law - Huang, Yau; Xing, Lijuan; Zhang, Haiwen (International Law E-Books Online, Collection 2024., 2024)
This policy-oriented jurisprudence presents the latest research findings on legal challenges faced by the international regulatory framework, as posed by the increasing deployment of uncrewed vessels at sea. It is the first publication that offe